A pesca na Amazônia ocidental: tratamento terminológico dos termos fundamentais - Fonseca, Agripino José Freire da [UNESP]; Babini, Maurizio [UNESP] (My University, 2013)
Fishing is a very important activity in terms of economic and social development throughout the Amazon region. Text reading this topic revealed the presence of a terminology not yet systematized and record little research and scientific publications on the terminology of this activity. This article aims at analyzing the key terms of fishing. At first, we present a brief history of this activity in Western Amazonia, particularly in Rondônia. The theoretical support was guided by Cabré (1999), with her Communicative Theory of Terminology, Aubert (1996), Barbosa (2002), Barros (2004), Biderman (2006), Babini (2006) and linguists as Baldinger (1966) and Pottier (1974) that reveal the details of linguistic analysis terminology. The creation of an electronic corpus, from texts of technical and documental discourse, theses and websites, composed the first stage of our work. Afterwards, collect the terms and fill the terminological records in our database. The terms were organized into a conceptual system with three notional fields: riverside community, type of fishing, gillnet fishing. Early results show that the set of terms collected is characterized by the strong presence of simple and complex terms, and less compound terms.

A pesca é uma atividade muito importante do ponto de vista econômico e social em toda região amazônica. A leitura de textos desse tema revelou a presença de uma terminologia ainda não sistematizada e o registro de poucas pesquisas e publicações científicas sobre a terminologia dessa atividade. Este artigo tem como objetivo geral analisar os termos fundamentais da pesca. Num primeiro momento, apresentaremos um breve histórico dessa atividade na Amazônia Ocidental, particularmente em Rondônia. O suporte teórico foi norteado por Cabré (1999), com sua Teoria Comunicativa da Terminologia, Aubert (1996), Barbosa (2002), Barros (2004), Biderman (2006), Babini (2006) e linguistas como Baldinger (1966) e Pottier (1974) que revelam os pormenores linguísticos de uma análise terminológica. A constituição de um corpus eletrônico, a partir de textos de divulgação técnica e documental, teses e sites, compôs a primeira etapa de nosso trabalho. Sucessivamente, coletamos os termos e preenchemos as fichas terminológicas de nossa base de dados. Os termos foram organizados em um sistema conceitual com três campos nocionais: comunidade ribeirinha, tipo de pesca, apetrecho de pesca. Os primeiros resultados mostram que o conjunto de termos coletados se caracteriza pela forte presença de termos simples e complexos, e menos termos compostos.
Keywords: Amazônia Ocidental; Pesca; Terminologia; Western Amazonia; fishing; terminology.